2012
DOI: 10.2334/josnusd.54.39
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatment on bond strength between an indirect composite material and a zirconia framework

Abstract: The present study evaluated the effect of various surface treatments for zirconia ceramics on shear bond strength between an indirect composite material and zirconia ceramics. In addition, we investigated the durability of shear bond strength by using artificial aging (20,000 thermocycles). A total of 176 Katana zirconia disks were randomly divided into eight groups according to surface treatment, as follows: group CON (as-milled); group GRD (wetground with 600-grit silicon carbide abrasive paper); groups 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
2
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 23 publications
6
21
2
6
Order By: Relevance
“…Alumina-blasting at a pressure of 0.2 MPa or higher led to significantly higher pre-and post-thermocycling bond strengths in the current study. This result contradicts those of earlier studies, in which alumina-blasting at pressures higher than 0.05 MPa 28) and 0.1 MPa 29) yielded superior and durable bond strengths. These conflicting results are likely principally due to the different experimental methods and materials used in the studies.…”
Section: Discussioncontrasting
confidence: 56%
“…Alumina-blasting at a pressure of 0.2 MPa or higher led to significantly higher pre-and post-thermocycling bond strengths in the current study. This result contradicts those of earlier studies, in which alumina-blasting at pressures higher than 0.05 MPa 28) and 0.1 MPa 29) yielded superior and durable bond strengths. These conflicting results are likely principally due to the different experimental methods and materials used in the studies.…”
Section: Discussioncontrasting
confidence: 56%
“…Zirconia treatment with 48%HF at 25 o C for 30 min resulted in a highly uneven surface compared with treatment under moderate conditions. These results are in contrast to previous studies on the etching of zirconia which used concentrations of HF ranging from 4.5-38% with etching times ranging from 1-12 min at room temperature 25,36,37,55) . These studies' results showed that HF had no effect on the zirconia surface and concluded that HF could not react with the dental zirconia ceramic surface because it is a glass-free material.…”
Section: Discussioncontrasting
confidence: 54%
“…It has been reported [29] that specimens blasted with aluminum oxide particles in various pressures increase the adhesive strength, which is kept durable between the zirconia and an indirect composite. They also reported that the surface roughness increases and chemically activates the adhesive surface, removing organic contaminants from the ceramic surface.…”
Section: Discussionmentioning
confidence: 99%